Supplementary material 1 from: Ancin-Murguzur FJ, Hausner VH (2020) Research gaps and trends in the Arctic tundra: a topic-modelling approach. One Ecosystem 5: e57117. https://doi.org/10.3897/oneeco.5.e57117 - Ancin-Murguzur, Francisco; Hausner, Vera (Zenodo, 2020)
Supplementary table 1